Academic leadership during the time of crisis: Success story of implementation success from traditional to online mode of education in a low-resource context - Saima Hamid; Shaheryar Naveed; Huma Ayub; Shoaib Akhtar (Cogent Social Sciences, 2023)
The beginning of 2020 was marked by the spread of the COVID-19 virus, which led to a global response in terms of lockdown measures by several countries and landed academics to offer online settings for teaching, research, and administrative activities. The situation led universities to respond quickly and effectively to address the needs of teachers, staff, students, and society. This study provides an overview of Active Implementation Frameworks (AIFs) adopted by a public-sector women’s university to overcome the hurdles due to the pandemic lockdown. The study provides evidence that AIFs are effective for implementing evidence-based models by promoting the development and deployment of innovations through implementation teams in a resource-constraint setting. The result of AIFs adoption by the university was the closure of the academic year on time along with global recognition of the university’s efforts during the pandemic by World Universities with Real Impact 2020. Fatima Jinnah Women University was ranked in the top 50 in crisis management category. This recognition is a testimony to the application of best practices for transforming higher education to not only survive but thrive in uncertain times and serves as a roadmap for public-sector universities to adapt to their contextual realities.